Dampak Keberadaan Kantong Parkir Angkutan Batu Bara terhadap Pendapatan Usaha Sektor Informal di Kecamatan Muara Tembesi - Daniel Alpajri; Junaidi Junaidi; Jaya Kususma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analysis the impact of the presence of coal transport parking areas on the Income of the Informal Sector, identify the most dominant factors influencing Income, and examine the socio-economic impact experienced by informal sector business actors in Muara Tembesi District. This study uses a quantitative approach with Multiple Linear Regression analysis and Classical Assumption Tests to test the hypotheses. Data were obtained through surveys of informal sector business owners around the parking areas. The dependent variable is Income, while the independent variables include Age, Education, Working Hours, Initial Capital, and Distance. Comparative descriptive analysis is used to validate socio-economic changes. Data analysis shows that working hours, initial capital, and distance have a positive and significant impact on the income of informal sector business actors, whereas age and education do not significantly affect the income of informal sector business actors. Descriptively, there has been massive welfare migration, indicated by the decrease in the proportion of low-income respondents from 60 percent to only 2 percent after the intervention. The presence of parking pockets has been proven to provide a positive and transformative economic impact for the informal sector. This impact is driven by increased production inputs (Capital and Working Hours). On the other hand, logistics activities generate negative external impacts in the form of dust pollution and security risks, which require strict regulation by the Local Government.